Regional-scale post-mining land-use transition: opportunities and challenges for industry and regulators - Cooper, C. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
How to manage successful ‘mine closure’ and achieve tenement relinquishment is a pressing question for miners, governments and communities, in many jurisdictions, particularly in regions exposed to a single commodity that may be near to exhausting reserves, or, across Australia’s coal fields; facing an industry approaching end of life. This paper explores key drivers and challenges for miners and governments, and the policy gaps that must be addressed to provide pathways for miners to confidently plan and execute closure, achieve tenement relinquishment, divest their landholdings in predictable, acceptable timeframes and facilitate regional economic transition planning. Key regulatory challenges such as the misalignment of operational approvals with closure activities and achievable outcomes, lack of policy regarding management of residual risk, and an absence of aggregated regional data to inform post mining land use planning, are all frustrating decision-making for Government, miners and developers. In Australian mining jurisdictions there is growing recognition that a new approach is required to create clear and reliable pathways to land use transition. While there are no strict regulatory barriers to miners collaborating with developers to modify closure planning toward alternative land uses, there are significant disincentives for both miners and developers including uncertainty regarding relinquishment timeframes and reluctance from the mining industry to relax control over all lease land until rehabilitation obligations are fulfilled. There is a ‘resigned acceptance’ by stakeholders that miners will remain the land stewards for up to 20 years following closure execution, frustrating the ability of strategic planners and developers to explore economic opportunities. Drawing on personal project experience including project managing the successful relinquishment, and transition of a Hunter Valley (NSW) coal mine to a major international tourist facility, this paper presents lessons learnt from contemporary relinquishment projects and policy initiatives from several jurisdictions that can contribute to improved pathways for industry and regulators to facilitate a collaborative approach to tenement relinquishment and regional transition planning.